Experimental study on the combustion characteristics of aluminized nitrate ester plasticized polyether solid propellant under high pressure. (April 2022) - Sha, Benshang; Na, Xudong; Xia, Zhixun; Yan, Xiaoting; Li, Yang; Huang, Liya
Abstract: Aluminized Nitrate Ester Plasticized Polyether high-energy solid propellant demonstrates bright application prospects due to its high-density specific impulse and satisfactory mechanical properties. The high-pressure experiment study were conducted on aluminized Nitrate Ester Plasticized Polyether to quantitatively investigate the burning rate characteristics at 1–7 MPa, and qualitatively analyse the agglomeration characteristics at 7 MPa. The burning rate experiment results indicate that the relationship between burning rate and pressure basically conforms to Vielle's burning rate law. When the ammonium perchlorate partice size decreases from 298 to 142 μm, the burning rate coefficient increases by 9.1% and the pressure index decreases by 7.6%. With the octogen particle size increasing from 15 to 150 μm, the burning rate coefficient and pressure index increases by 15.0% and 9.8%, respectively. When the aluminum particle size decreases from 30 to 16 μm, the burning rate parameters remain unchanged. While the aluminum particle size decreases from 16 to 2 μm, the burning rate coefficient increases by 20.5% and the pressure index decreases by 18.6%. The burning rate is significantly affected by octogen particle size and aluminum particle size has the vital influence on burning rate coefficient and pressure index. The agglomeration process and second mergence phenomenon at 7 MPa were observed for the first time and the agglomeration process mainly happens on the burning surface and above the burning surface under high pressure. Qualitative analysis shows that high pressure reduces the retention time of agglomerates on the burning surface and intensifies the combustion process of agglomerates, and coarse octogen can effectively reduce the agglomeration particle size at 7 MPa. The conclusions can provide insights into the influence of Nitrate Ester Plasticized Polyether composition on burning rate and the effect of high pressure on the agglomeration process in the motor. Highlights: Influence of the particle size of Al, HMX, and AP on the burning rate parameters was quantitatively analyzed at 1–7 MPa. The 2 μm Al can decrease pressure index and increase the burning rate coefficient significantly. Coarse HMX can increase the burning rate and pressure index, and decline the agglomeration particle size. The Al agglomeration and combustion process at 7 MPa were observed for the first time. The agglomeration process at high pressure mainly happens on or above the burning surface.